(untitled) (International Journal of Engineering and Computer Science, 2016)
The agile methods, such as Scrum and Extreme Programming (XP), have been a topic of much discussion in the software community over the last few years. While these have gained importance in the industry because of their approach on the issues of human agility and return on investment, usually within a context of small-to-medium size projects with significant requirements volatility, the ones who do not support these methods have expressed serious concerns about the effectiveness of the methods. Scrum attempts to build the work in short iterations where each iteration consists of short time boxes. This paper reviews several papers on Scrum, its framework including its artifacts and the ceremonies which are involved. This paper gives an insight of the Scrum Methodology to any beginner